Small And Medium-Sized Enterprises in Developing Countries And the Coronavirus Pandemic - Krzysztof MARECKI (Communications of International Proceedings, 2021)
The outburst of the Covid-19 pandemic has exacerbated the demanding situations confronted through Small and Medium-sized Enterprises (SMEs), specifically in developing countries. The main sufferers of the COVID-19 eruption are small, and medium-sized enterprises (SMEs). These article pursuits to evaluate the effect of the COVID-19 outbreak on those enterprises. Certainly, they have been the maximum laid low with lockdowns, tour regulations, and different methods taken through governments to incorporate the pandemic, in particular given their restrained investments. This word opinions administrations’ responses to assist SMEs inside the face of COVID-19, and reflects feasible paths to in addition assist them faucet into springing up digitalization and marketplace get right of entry to occasions.
Keywords: Covid-19 pandemic; small and Medium-sized Enterprises (SMEs); Crisis; Developing countries